The process for the production of high phospholipid containing eicosanoids and soluble oligopeptides from the Oyster. sp. - Tra, Le Thi Thanh; Toan, Tran Quoc; Dung, Dao Thi Kim; Long, Pham Quoc (Vietnam Journal of Marine Science and Technology, 2020)
Oysters could be found in seashore and estuarine areas and is regarded as a valuable export product with high economic value. In addition, the oysters could serve as an efficient assimilator of nutrients and potential source of polyunsaturated fatty acids (PUFA), mainly omega-3 fatty acids, which have been found to be responsible for a wide array of health benefits. In this paper, we report a process for the production of high phospholipid containing eicosanoids and soluble oligopeptides from the Oyster. sp. This result shows phospholipid layer containing high eicosanoids with 34.4% and soluble oligopeptides containing 8 essential acid amides. 19.53 g histidine per 100 g oligopeptides pointed out that hydrolyzed oysters are highly nutritional and valuable pharmacological products.